2016
DOI: 10.1177/1362168815574145
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and practices of Brazilian EFL teachers regarding pronunciation

Abstract: Interest in pronunciation learning and teaching has increased significantly in the past few years. Studies and resources in the area have proliferated, but it is important to know whether they have influenced teachers of English as a foreign language (EFL) and English as a second language (ESL). The purpose of this study was to investigate the beliefs and practices of Brazilian EFL teachers. Convenience and snowball sampling were employed to recruit 60 participants, who completed an online survey on pronunciat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
77
4
7

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 29 publications
21
77
4
7
Order By: Relevance
“…A clear finding across both data sources was that very little instructional time was allocated to pronunciation teaching. These results are in line with findings from previous surveys in EFL/ESL and foreign language contexts (e.g., Buss, ; Foote et al, ; Huensch, ) and classroom observations in ESL contexts (Foote et al, ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…A clear finding across both data sources was that very little instructional time was allocated to pronunciation teaching. These results are in line with findings from previous surveys in EFL/ESL and foreign language contexts (e.g., Buss, ; Foote et al, ; Huensch, ) and classroom observations in ESL contexts (Foote et al, ).…”
Section: Discussionsupporting
confidence: 92%
“…Much of the research on the amount and type of pronunciation instruction has come from surveys of instructors. Studies have shown that a majority of respondents who taught ESL (Foote et al, ); EFL (Buss, ); and French, German, or Spanish introductory language courses in the United States (Huensch, ) reported that they thought such instruction was important and that they addressed pronunciation in their lessons, although they devoted little instructional time to doing so. For example, Foote et al (2011, p. 11) calculated the average amount of class time spent on pronunciation to be 6%.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, other issues such as learners' goals, and their L1 backgrounds, should also be considered when choosing an L2 English pronunciation model. The teaching and learning of English language pronunciation should be guided and aided by useful tools such as phonetic transcription, for the more advanced learners, and other resources which are now more accessible such as computer software, mobile apps, and internet tools (Buss, 2016).…”
Section: Resultsmentioning
confidence: 99%